COMMON GRAMMATICAL ERRORS IN CONSTRUCTING ENGLISH NOUN CLAUSES MADE BY THIRD SEMESTER STUDENTS OF ENGLISH LANGUAGE STUDY PROGRAM OF STKIP NIAS SELATAN - Senadaman Wau (Jurnal Education and Development, 2020)
This research aimed at identifying the common errors in constructing English noun clauses made by the third semester students of English Language Education Study Program of STKIP Nias Selatan. This research employed a descriptive qualitative research design. Documentation was used as the techniques to collect the data of the research. The number of the participants were 59 students. The result of data analysis shows that the students commonly made the errors on omission, addition, misformation, and misordering in constructing noun clause begun with subordinator –that, question word, and whether/if. The findings of this research are expected to be advantageous reference to improve errors made in constructing noun clause as dependent clause and to study grammar more.